Orban's oral histology and embryology - Bhaskar, S. N. 1923- (Surindar Nath) (New Delhi : CBS publishers & distributors, 1990)
1 development of face and oral cavity. 2 development and growth of teeth. 3 enamel. 4 pulp. 5 dentin. 6 cementum. 7 periodontal ligament. 8 maxilla and mandible (alveolar process). 9 oral mucous memrane. 10 salivary glands. 11 tooth eruption. 12 shedding of deciduous teeth. 13 temporomandibular joint. 14 maxillary sinus. 15 histochemistry of oral tissues.
Includes index.
Keywords: Embryology, Human; Histology; Mouth -- anatomy & histology; Mouth -- embryology; Tooth -- anatomy & histology